Photodynamic Therapy for the Treatment of Basal Cell Carcinoma: A Comprehensive Review of Randomized Controlled Trials - Ioannis-Alexios Koumprentziotis; Natalia Rompoti; Konstantinos Liopyris; Electra Nicolaidou; Alexander Stratigos (Mattioli1885, 2024)
Introduction: Basal cell carcinoma (BCC) is the most common skin cancer worldwide and has been reported to have a rising incidence in the last years. Multiple therapeutic modalities are approved for the treatment of BCC, making it difficult for physicians to choose the most suitable option for every patient. Photodynamic therapy (PDT) using either 5-aminolevulinic acid (ALA) or methyl aminolevulinate (MAL) as photosensitizing agents is an established treatment option for low-risk BCC. Objectives: This review aims to summarize the available evidence from randomized clinical trials (RCTs) that utilize either ALA or MAL PDT and compare it with other treatment modalities. The main outcomes related to the effectiveness, adverse events, cosmetic outcomes and pain sensation, along with data from long-term follow-ups will be presented and discussed. Methods: Thorough literature searches were conducted through the electronic databases ClinicalTrials.gov and Pubmed/MEDLINE from inception up to 28 March 2023. Only studies in English were included. All relevant data were extracted accordingly from the eligible studies. Results: Eight RCTs included superficial BCC (sBCC) alone, 7 included nodular BCC (nBCC), 2 included both sBCC and nBCC and 1 included BCC of unspecified subtype. Follow-up duration ranged from 3 months to 5 years. Both ALA-PDT and MAL-PDT demonstrated acceptable efficacy, adverse events, cosmetic outcomes and pain sensation while no major differences were observed between them. PDT was less effective than surgery but with better reported cosmetic outcomes. Conclusions: PDT is a safe and efficacious treatment option for sBCC and to a lesser extent nBCC.